Assessment of factors associated with linkage to care amongst adults accessing HIV services at Bwaila hospital, Lilongwe district, Malawi. - Gondwe, Clifton Muvwala (2021)
Despite the policy progress made in Malawi about HIV and AIDS, the prevalence rate remains among the highest in the world. Despite many people being tested HIV positive not all have been linked to HIV care. Linkage to care is a crucial early step in successful HIV treatment. Linkage to HIV care is still a challenge in Malawi as 32% is not yet linked to care. This group may pose a threat of transmitting the infection to the population. Currently the country is striving to meet the 90.90.90 UNAIDS target The main objective of the study was to assess factors associated with linkage to care amongst adults accessing HIV services at Bwaila Hospital in Lilongwe District.This was a descriptive cross-sectional study that employed qualitative methods. Eighteen in-depth interviews were conducted with clients above 18 years old and 2 focus group discussions with Health Providers at Bwaila Hospital. Purposive sampling method was used to recruit study participants. Thematic analysis was used to analyze data. Findings indicate that linkage to care is affected by one‟s perception towards Antiretroviral Therapy initiation, physical escort of clients by providers, integration of services, existence of support partners, shortage of staff leading to high workload, poor coordination of services at the facility and distance to the facility. Interventions aimed at improving linkage to care in HIV services should focus on integration of health services. In addition, additional human resource and ease of access to health services should also be considered